WEB Web Blog Media Development in Women's Fashion Lessons - Bahri, Halimul; Farihah; Anggraini, Yudhistira; Panggabean, Frinches E.R (Jurnal Pedagogi dan Pembelajaran, 2023)
The difficulty of understanding the material for making bustiers just from the teacher's explanation makes students look for more material on the internet so they can repeat the learning independently. However, the material obtained was not made in the correct systematic way. Apart from that, learning media for bustier making that is capable of presenting the material concretely is still very limited. This research aims to develop Web blog media and test the suitability of Web blog media for women's fashion subjects. This type of research is research and development (R&D) research, and this research uses the ADDIE development model. Media development validation was carried out by 3 material experts and 3 media experts. A needs analysis shows that 94% of students agree with the development of a web blog. The results of the material expert assessment on the learning aspect were 89%, the material aspect was 92%, and the overall average assessment was 90.5% in the Very Decent category. The results of the media expert's assessment of the usability aspect were 94%, the media design aspect was 96%, and overall, the average was 95% in the Very Appropriate category. The results of limited trials carried out by 5 students obtained an average of 87.1% in the very good category. Advanced field trials carried out by 36 students obtained an average rating of 89.5% in the very good category. Based on the results of validation and media testing, it can be concluded that the Web blog media developed is very suitable for use as a learning medium for bustier-making material in the women's clothing subject. The development of Web blog media can make it easier to deliver material and make students more interested in repeating learning so that it can increase students' understanding of the correct bustier making.